The Effect of Effleurage Massage on Reducing Dysmenorrhea in Adolescent Girls in Sukarama Village, Cianjur Regency, Indonesia - Lailatun, Lailatun (Arkus, 2023)
Effleurage massage has several potential benefits that may help reduce symptoms of dysmenorrhea in adolescent girls, such as increasing blood circulation to the abdominal area, relieving muscle tension, and promoting relaxation. This study aims to determine the effect of effleurage massage on reducing dysmenorrhea in adolescent girls in Sukarama Village, Cianjur Regency, Indonesia. This study is experimental research with a pre and post-test approach. This study uses primary data obtained from direct observation of respondents. A total of 30 research subjects took part in this study. This study shows that massage effleurage intervention reduces pain intensity in dysmenorrhoea sufferers. There was a decrease in pain intensity after effleurage massage, and it was stated to be statistically different, p<0.05. In conclusion, effleurage massage has an effect on reducing dysmenorrhea in young women in Sukarama Village, Cianjur Regency, Indonesia.